Complete conditioning for soccer - Alexander, Ryan (Human Kinetics, 2021)
"This book provides readers with a comprehensive overview on soccer conditioning for players of all levels. A heavy emphasis is placed on position specificity (e.g., conditioning for midfielders, conditioning for forwards, etc.) and injury prevention and management"--